(untitled) (Revista Cientifica Ingenio Magno, 2020)
The article presents the results of the effect of iron oxide on the mechanical characteristics of an asphalt mixture prepared with an AC 80-100 asphalt and stone aggregate of the Peace of the River crushed quarry for the construction of a rolling layer colored; in order to improve harmony, aesthetics and road safety. To carry out the above, the design of six asphalt mixtures was carried out a conventional evaluating percentages from 4.0 to 6.5 of asphalt cement to determine the optimal percentage of asphalt and from this value five mixtures with percentages were made 2 to 10 pigment, under the Marshall methodology. Based on this data, tests were carried out on resistance to plastic deformation, susceptibility to moisture damage, resilient module, fatigue resistance and British pendulum test. An optimal asphalt percentage of 6% was determined, which was used as a fixed value to obtain the optimal percentage of iron oxide of 5%, generating increasing, decreasing and erratic behaviors for preliminary design variables and with respect to tests significant improvements are made in plastic deformation, resilient module and fatigue resistance.